(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2026)
The translation of science fiction texts requires more than linguistic competence; it demands complex cognitive engagement with imaginative, speculative, and often unprecedented concepts. This paper investigates cognitive approaches to translating science fiction, focusing on how translators interpret, process, and reconstruct meaning across languages. Drawing on schema theory, conceptual metaphor theory, and relevance theory, the study demonstrates that translation in this genre involves dynamic mental modeling and creative decision-making. The research argues that successful translation depends on the translator’s cognitive flexibility, domain knowledge, and ability to balance scientific accuracy with narrative creativity.